2012
DOI: 10.2519/jospt.2012.3919
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Structural Properties of the Collateral Ligaments of the Human Knee

Abstract: T he passive stability of the knee is primarily provided by a complex system of intra-and extra-articular ligaments that resist anterior and posterior translation, abnormal tibial rotation, and varus and valgus rotation. Functionally, the medial collateral ligament complex (MCL) acts as the primary restraint to valgus rotation of the tibia, providing as much as 80% of the restraining force to valgus loads. 11 The lateral collateral T T STUDY DESIGN: Controlled laboratory study. T T BACKGROUND:Varus knee instab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 41 publications
(39 reference statements)
2
53
1
Order By: Relevance
“…1). The stiffness coefficients of the anterior-lateral PCL, posterior-medial PCL, LCL, anterior MCL, and posterior MCL were set at 102, 102, 59, 63, and 63 N/mm, respectively, based on reported values (Harner et al, 1995;Robinson et al, 2005;Sugita and Amis, 2001;Wilson et al, 2012). The length and slack of each ligament throughout its range of motion were finely adjusted so that the length patterns of the ligaments were similar to those reported by a previous cadaver study (Fig.…”
Section: Methodsmentioning
confidence: 96%
“…1). The stiffness coefficients of the anterior-lateral PCL, posterior-medial PCL, LCL, anterior MCL, and posterior MCL were set at 102, 102, 59, 63, and 63 N/mm, respectively, based on reported values (Harner et al, 1995;Robinson et al, 2005;Sugita and Amis, 2001;Wilson et al, 2012). The length and slack of each ligament throughout its range of motion were finely adjusted so that the length patterns of the ligaments were similar to those reported by a previous cadaver study (Fig.…”
Section: Methodsmentioning
confidence: 96%
“… a Pang and Ying, 2006, b Mello et al, 2006, c Cook et al, 1998, d Dundon et al, 2012, e Stenroth et al, 2012, f Wiesinger et al, 2016, g Wilson et al, 2012, h Zooker et al, 2012 …”
Section: Tablementioning
confidence: 99%
“…Likewise, Woo et al (1991) found that human ACL stiffness and ultimate force were decreased with age using three age groups: 22-35 years, 40-50 years, 60-97 years. More recent studies of the human medial collateral ligament (MCL) have cautioned that, similar to the ACL, strength and stiffness that were measured only assessing older MCLs may underestimate the strength and stiffness of younger MCLs (Robinson et al, 2005;Wilson et al, 2012).…”
Section: Introductionmentioning
confidence: 98%